Psicologia do Desenvolvimento no Currículo de Formação de Professores - Maria Lins (Universidade Estadual Paulista Júlio de Mesquita Filho, 2012)
This article focuses on the role of the study of Developmental Psychology in training teacher courses' curriculum. The objective of this article is to emphasize the importance of Developmental Psychology for all those people who will be responsible for children and adolescent education. The method was to analyze the nature and aims of Developmental Psychology as a field of knowledge for future school teachers. Developmental Psychology was considered concerning cognitive, affective, social, moral and physical realms. Theories of Developmental Psychology are the basis of educational practice in school and because of this it is suggested that it should be given more attention to Developmental Psychology in 44Maria Judith Sucupira da Costa Lins. Psicologia do Desenvolvimento no Currículo de Formação de...training teacher courses' curricula. As a conclusion it can be said that Developmental Psychology is indispensable for all those who intend to work at school and especially for teacher. Theories of Developmental Psychology are basic to educational practice. Contributions of Developmental Psychology are assessed as main tools for teachers in all different fields of knowledge.